Valuing self-love: lived experiences in work-life balance of special education teachers - Saldivar - Henke, Mary Jane (Technium Social Sciences Journal, 2023)
Sustaining work life-balance of special education teachers is not easy, for there are factors that hinder such, particularly if the question of self-love is to be maintained. This qualitative phenomenological study determined the dimensions of the lived experience of special education teachers as to what factors affect their sustaining work balance and how they faced such. Fifteen (15) purposely selected participants comprised the sample for this study. They were chosen through the following criteria namely: licensed special education teachers; with no less than three years of working experience in a special education schools situated in Muntinlupa City; married or unmarried; and have expressed sentiments regarding stress that they are experiencing connected with their work, family, social life and health aspects. Nine (9) recurring themes emerged from the verbatim interviews center on prayer, salary, sense of humor, relationship with parents of students, training, health, support system, stress management, setting boundaries between personal and professional self. These resulted in creating innovative teaching practice in order to sustain work and life balance.